Auto-adaptive positive airway pressure improves lung function and arterial stiffness parameters in patients with severe obstructive sleep apnea syndrome over a 1 year follow-up. (28th December 2020) - Milicevic, Tanja; Katic, Josip; Milovac, Stjepanka Nakic; Matetic, Andrija; Aljinovic, Jure; Dogas, Zoran; Gunjaca, Grgo
Abstract: Objective : Auto-adaptive positive airway pressure (APAP) is an emerging therapeutic modality for obstructive sleep apnea (OSA) patients. However, their associated physiological effects have not been well-defined. Therefore, we aimed to investigate the impact of a 1 year APAP treatment on lung function and arterial stiffness parameters. Approach : This study enrolled male patients with newly diagnosed severe OSA who have undergone APAP treatment. A total of 35 patients completed a 1 year follow up . Blood pressure, arterial stiffness (PWV, cAIx, pAIx, cSBP), and lung function readings (FEV1, FVC, FEV1 /FVC, PEF) were obtained basally and after 1, 3, 6, and 12 months of treatment. Main results : A gradual increase in FEV1 has been observed over the follow-up (2.92 ± 0.88 versus 3.07 ± 0.92 versus 3.18 ± 0.93 versus 3.28 ± 0.93 versus 3.41 ± 0.97 L), while PWV showed a gradual decrease over the follow-up (9.72 ± 1.64 versus 9.32 ± 1.73 versus 8.89 ± 1.65 versus 8.53 ± 1.61 versus 8.46 ± 1.60 m s −1 ), as measured by absolute values. Linear mixed effects model analysis revealed a statistically significantly higher FEV1 values (coefficient of 0.11, 0.20, and 0.33 for 3rd month, 6th month, and 12th month, respectively, P  < 0.001) and lower PWV values (coefficient of −0.69, −0.63, and −0.34 for 3rd month, 6th month, and 12th month, respectively, P  < 0.001), after the initiation of APAP treatment. Significance : We conclude that APAP treatment improves main lung function and arterial stiffness parameters in male patients with severe OSA over a 1 year follow-up .